2021
DOI: 10.1007/s12603-021-1668-5
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Prevalence Rates among Dutch Nursing Home Residents: What Has Changed over One Decade? A Comparison of the Years 2009, 2013 and 2018

Abstract: Objectives To assess changes in prevalence of malnutrition and its associated factors among people living in Dutch nursing homes in 2009, 2013 and 2018. Design Secondary data analysis of the International Prevalence Measurement of Care Quality (LPZ) study. Setting Dutch nursing homes. Participants Residents living at a psychogeriatric or somatic ward in Dutch nursing homes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…Residents included in our study were comparable to residents included in the Dutch National Prevalence Measurements of Care Problems 2018 (LPZ), a representative cohort of Dutch nursing-home residents. The overall age of the residents in our study, 85.0 (SD:7.4) years, was slightly higher than in LPZ in which the residents were 83.2 (SD: 9.5) years old [271] and BMI (26.0 (SD:5.0) kg/m 2 ) was comparable with LPZ (25.1 (SD:6.3) kg/m 2 ). Prevalence of malnutrition risk (based on SNAQ RC ) was also comparable to LPZ (both 24% at high risk) [272].…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Residents included in our study were comparable to residents included in the Dutch National Prevalence Measurements of Care Problems 2018 (LPZ), a representative cohort of Dutch nursing-home residents. The overall age of the residents in our study, 85.0 (SD:7.4) years, was slightly higher than in LPZ in which the residents were 83.2 (SD: 9.5) years old [271] and BMI (26.0 (SD:5.0) kg/m 2 ) was comparable with LPZ (25.1 (SD:6.3) kg/m 2 ). Prevalence of malnutrition risk (based on SNAQ RC ) was also comparable to LPZ (both 24% at high risk) [272].…”
Section: Discussioncontrasting
confidence: 58%
“…This is in line with the large group of community-dwelling older adults that already displays early determinants of malnutrition (chapters 2-4). Another reason for a low age-specific BMI could be the high prevalence of cognitive problems in (newly admitted) residents of long-term care facilities [271]. Doing grocery shopping and preparing food are among the first skills that are lost in older adults suffering from cognitive decline [188], which could lead to an inadequate intake.…”
Section: Malnutrition In Long-term Care Facilities Malnutrition Scree...mentioning
confidence: 99%
See 1 more Smart Citation
“…Residents in our sample were relatively younger (83.1 years) compared to the average Dutch resident in 2019 (85.0 years) [ 24 ]. Compared to another Dutch representative cohort [ 25 ], our residents had a comparable BMI (24.8 vs. 24.7 kg/m 2 ), but the number of diseases was higher in our population (4.5 vs 3.0), which is probably explained by the fact that we also included health-related problems. In general, our population seems to reflect the average population in Dutch LTCFs.…”
Section: Discussionmentioning
confidence: 68%
“…Everink et al compared the prevalence of malnutrition among nursing home residents in the Netherlands in 2009, 2013, and 2018 [28]. They reported that the prevalence of malnutrition was relatively stable at approximately 16% and that it was unclear whether nursing staff were adequately aware of malnourished (at-risk) residents and the interventions that could be implemented to reduce this occurrence.…”
Section: Nutrition Supports For Preventing Malnutritionmentioning
confidence: 99%